Prediction of efficacy of gonadotropin releasing hormone agonist trigger for final oocyte maturation through post-trigger 12-hour luteinizing hormone, follicle stimulating hormone and progesterone levels in COS: a prospective study - Agarwal, Sonal; Krishna, Deepika; Pranesh, Gautham; Rao, Kamini A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Circulating levels of luteinizing hormone (LH), follicle stimulating hormone (FSH) and progesterone (P4) in serum after administration of gonadotropin releasing hormone agonist (GnRHa) trigger for final oocyte maturation are found to be predictive of oocyte maturity. This prospective study was conducted at a tertiary care centre to evaluate relationship between serum LH, FSH and P4 levels at 12-h post-trigger and oocyte maturity rate and to predict which hormone has maximum sensitivity and specificity for appropriate oocyte maturation. Methods: Women at risk of ovarian hyper-stimulation syndrome who underwent either autologous or donor IVF cycle treated with flexible GnRH antagonist protocol were taken as participants of the study. GnRHa as trigger for final oocyte maturation was given. After 12 hours of agonist trigger, blood sample was drawn to assess LH, FSH and P4 levels in serum. Continuous variables were expressed as mean±SD. Independent sample t test was used for continuous variables which were normally distributed and Mann-Whitney U test for data not normally distributed. Main outcome measures were number of oocytes retrieved, oocyte maturity rate, fertilization rate, cleavage rate and grade of embryos. Results: There was a statistically significant reduction in number of retrieved oocytes, maturity rate, fertilization rate and grade 1 embryos with a concentration of serum LH and P4 less than the cut off value (p < 0.05). Conclusions: Serum LH and P4 level less than the cut off value at 12-hour post-trigger with GnRHa is associated with a dramatically less oocyte maturity rate and fertilization rate.